THE JARGONS USED BY TENGANAN VILLAGE PEOPLE IN GRINGSING WEAVING - Dewi, Agung Ayu Putu Septia; Ramendra, Dewa Putu; Mahendrayana, Gede (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Language is a system that mediates and types of vocalizations used by a community to communicate to understand each other. Language also has many varieties. This diversity is influenced by many factors, such as being influenced by a known place by age, gender, social status, and type of work. One variety of language is jargon. This study aims to analyze the jargon of meaning used by the people of Tenganan Village in weaving grinning. The design of this research is a qualitative descriptive design. The method used is observation and interviews. The observation method was carried out to observe the state of Tenganan village. The interview method was conducted to interview two weavers in Tenganan village to provide information regarding the jargon they use. The results showed that Tenganan Village people used fifty-six jargon to bring weaving. Based on fifty-six jargon, they are categorized into four types. The first type is jargon based on yarn processing, consisting of twenty jargon. The second type is jargon based on the weaving process, which finds three jargon. The third type is jargon based on naming tools and materials that find fifteen jargon. The fourth type is jargon based on the naming of eighteen motifs. Each jargon has a meaning that is used to facilitate communication between weavers in producing grinding weaving.